Differential Variation in Non-structural Carbohydrates in Root Branch Orders of Fraxinus mandshurica Rupr. Seedlings Across Different Drought Intensities and Soil Substrates - Ji, Li; Liu, Yue; Wang, Jun; Lu, Zhimin; Zhang, Lijie; Yang, Yuchun (Frontiers in Plant Science, 2021)
Nonstructural carbohydrates (NSCs) facilitate plant adaptation to drought stress, characterize tree growth and survival ability, and buffer against external disturbances. Previous studies have focused on the distribution and dynamics of NSCs among different plant organs under drought conditions. However, discussion about the NSC levels of fine roots in different root branch orders is limited, especially the relationship between fine root trait variation and NSC content. The objective of the study was to shed light on the synergistic variation in fine root traits and NSC content in different root branch orders under different drought and soil substrate conditions. The 2-year-old Fraxinus mandshurica Rupr. potted seedlings were planted in three different soil substrates (humus, loam and sandy-loam soil) and subjected to four drought intensities (CK, mild drought, moderate drought and severe drought) for two months. With increasing drought intensity, the biomass of fine roots decreased significantly. Under the same drought intensity, seedlings in sandy-loam soil had higher root biomass, and the coefficient of variation of fifth-order roots (37.4%, 44.5% and 53.0% in humus, loam and sandy loam soil, respectively) was higher than that of lower-order roots. All branch order roots of seedlings in humus soil had the largest specific root length and specific root surface area, in addition to the lowest diameter. With increasing drought intensity, the specific root length and average diameter of all branch orders increased and decreased, respectively. The fine roots in humus soil had a higher soluble sugar content and lower starch content compared to the loam and sandy-loam soil. Additionally, the soluble sugar and starch contents of fine roots showed decreasing and increasing tendencies with increasing drought intensities, respectively. Soluble sugar and starch explained the highest degree of total variation in fine root traits, which were 32.0% and 32.1%, respectively. With increasing root order, the explanation of the variation in root traits by starch decreased (only 6.8% for fifth-order roots). The response of different root branch order fine root morphological traits of F. mandshurica seedlings to resource fluctuations ensures that plants maintain and construct the root development in an economical way to obtain more resources.